Perancangan Alat Otomatisasi Sistem Monitoring Dan Kontroling Tinggi Permukaan Air Sungai Sebagai Peringatan Dini Terjadinya Banjir - Suparman Suparman; Eka Suhartanto; Yahya Ibnu Shina (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
The frequent occurrence of floods caused by overflows of river water indicates a lack of supervision of water level activities, even though the impact of the flood is very detrimental to the community. Therefore we need a business that can monitor and control water capacity, one form of business that can be made is by designing a device that can monitor and control the water level using sensors and microcontrollers. The way this tool works is as a means of detecting water level distances using an SRF 05 sensor by sending a signal to the Arduino uno microcontroller to process the data and then output from the LCD in the form of letters and numbers, the LED indicator which indicates the water level is a warning sign for this system. This system has three levels of water activity levels, namely at level 1 marked with a green LED then at level 2 marked with a blue LED then at level 3 marked with a red LED, the LED connected to the buzzer will provide a warning sign in the form of a siren/alarm that the water has been at the highest level and the relay has come alive with a red color. The design of an automated monitoring and control system for water level using sensors and microcontrollers has been successfully carried out. The purpose of this research is to design a tool that can monitor the water level in real time and is also based on a microcontroller. The calibration results show that the SRF 05 sensor has an average water level measuring instrument accuracy of 99.67% and has an average relative error of 0.33%. The results of this study indicate that the design of the tool that has been made has worked well as a monitoring and control system for water level using the Arduino Uno microcontroller.